The Domino Effect of Increasing the Cost Of Hajj in Islamic Economic Perspective - Sholatiah, Sholatiah (Universitas Siliwangi, 2024)
Introduction to The Problem: The government has announced that there will be an increase in the cost of Hajj for departure in 2024 or 1445 H. Meanwhile, going on Hajj is the dream of every Muslim in the world. The cost of performing Hajj can be an economic burden for many people who wish to fulfill this last pillar of Islam. So the phenomenon of rising Hajj costs has become an increasingly fundamental and urgent issue as it creates significant challenges in Islamic economics.Purpose/Objective Study: The purpose of this study is to analyze the domino effect of the increase in the cost of the Hajj pilgrimage from an Islamic economic perspective.Design/Methodology/Approach: This research uses a literature study method with a qualitative approach. Data collection techniques are sourced from online news such as information from the Ministry of Religion to get the latest news related to the increase in BPIH fees and using secondary data obtained from websites, scientific articles, books and other reliable sources. Then the data is analyzed in accordance with the discussion related to the impact of the increase in the cost of Hajj using the theory of Islamic economic principles.Findings: The results of the study found several impacts due to the increase in the cost of Hajj, both direct and indirect impacts, namely: it can cause financial difficulties for prospective pilgrims, dissatisfaction among the public that can trigger negative reactions against the government or institutions responsible for the policy, will experience a reduction in the social and economic funds they have accumulated, raising questions about the government's responsibility in ensuring the accessibility of Hajj for all citizens. The hike in Hajj fees also highlights the importance of Islamic economic education and public awareness of Islamic economic principles involving justice, brotherhood, and solidarity.